TINDAK PIDANA EKONOMI DALAM FIKIH PIDANA ISLAM - J Jaenudin; Enceng Arif Faizal (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2020)
This article aims to answer the economic criminal sanctions in Islamic criminal jurisprudence. Islamic law has regulated criminal acts that are clear and described in the field of jinayah. However, it is necessary to specifically classify economic criminal sanctions. This research uses literature research with content analysis techniques in examining the development of economic crimes in Islamic criminal jurisprudence. The results showed that the arrangement of the fingers was clearly regulated through texts which were called hudud and outside texts which were categorized as ta'zir. This classification is based on whether there are sanctions provisions in the text. Economic crimes in fiqh jinayah are grouped: economic crimes in the hudud category, namely sariqah or robbery, and hirabah or robbery. Second, ta'zir economic crimes, namely corruption, money laundering, smuggling, counterfeiting, fraud, and environmental pollution, the sanctions are given to the level of benefit and ulil amri.